Peran Pengendalian Internal Terhadap Persediaan Barang Pada PDAM Tirta Dharma Salatiga - Fibri Yuliani; Siti Afidatul Khotijah (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
Inventory of goods is an important asset for the survival of the company. In large-scale inventory management, companies must manage inventory both in planning goods and in controlling to prevent inventory loss and damage to an inventory. Thus it is necessary to have internal controls that are carried out periodically with the aim of the company's existing inventory being managed carefully. It is possible that the company's assets will be well preserved. This study aims to determine the role of internal control over inventory at PDAM Tirta Dharma Salatiga. The method used in this research is a qualitative method. The source of the data used by the author in the preparation is primary data. The data collection techniques used were interview techniques and direct research to the object for one month. The results of this study indicate that the internal control system for inventory goods at PDAM Tirta Dharma Salatiga as a whole is effective. However, the risk assessment component shows ineffective results because there are several items that have accumulated in the warehouse such as knives, boughs, and sockets that are stored in the barrel and if the inventory in the barrel is reduced, new supplies will be added. This can cause the knife, bough, and socket stock in the barrel earlier to toughen up.